Signaling versus Costly Information Acquisition - Helmut Bester; Matthias Lang; Jianpei Li (Center for Economic Studies and ifo Institute (CESifo), 2018)
In Spence's (1973) signaling by education model and in many of its extensions, firms can only infer workers' productivities from their education choices. In reality, firms also use sophisticated pre–employment auditing to learn workers' productivities. We characterize the trade–offs between signaling by workers and costly information acquisition by firms. Information acquisition is always associated with (partial) pooling of worker types, and education is used as a signal only if relatively few workers have low productivity. Our analysis applies also to other signaling problems, e.g. the financial structure of firms, warranties, and initial public offerings.
Keywords: D82; D86; 330; signaling; information acquisition; auditing